Transformation of the Earth Charity Tradition in the Era of Globalization: An Ethnographic Study of the Sambikerep Village Community, Surabaya - Agustin, Riska; Mesra, Romi (LANGGAM: International Journal of Social Science Education, Art and Culture, 2024)
The Earth Charity Tradition is a form of local cultural tradition that continues to be preserved in the lives of agricultural communities in Indonesia, particularly in Sambikerep Village, Surabaya. However, in the context of globalization, many local traditions are facing significant challenges. This ethnographic study is crucial in delving deeper into the transformations that have occurred in the significance and value of Sedekah Bumi within Sambikerep Village, Surabaya. The primary objective of this research is to provide a comprehensive understanding of how local communities navigate the balance between tradition and modernity, while simultaneously preserving their cultural identity in the face of globalization. This research employs qualitative research methods, including participant observation, interviews, and documentation, to gather data. The qualitative data analysis involves data reduction, presentation, and conclusion drawing. The theoretical frameworks employed in this research are social construction theory and hybridity theory. The findings of this research demonstrate that the advent of globalization and its associated modernization values have transformed Sedekah Bumi from a purely spiritual event into an entertainment experience that incorporates social activities requiring participation and cooperation from all village residents. This transformation involves the integration of traditional elements with modern aspects, resulting in a vibrant cultural performance that does not compromise the original cultural heritage.